Autophagy is a key factor in maintaining the regenerative capacity of muscle stem cells by promoting quiescence and preventing senescence - Wen, Xin (Autophagy, 2016)
Autophagy, a highly regulated cellular degradation and recycling process, can occur constitutively at a basal level, and plays an essential role in many aspects of cell physiology. A recently published study (see the related punctum in Autophagy, Vol. 12, No. 4) suggests that basal autophagy is also important for maintaining the regenerative capacity of muscle stem cells, and that the decline of autophagy with aging is the cause of entry into senescence from quiescence in satellite cells.